Awareness of vaccine-preventable diseases and self-reported immune status of Swiss dental healthcare workers (Swiss Medical Weekly, 2021)
INTRODUCTION: Dental healthcare workers are exposed to various infectious agents that may present an occupational risk. Although vaccinations rank among the most cost-effective health measures, vaccine hesitancy is present among healthcare workers.METHODS: A structured anonymous questionnaire was completed by 1111 dental healthcare workers – dentists, dental hygienists, prophylaxis assistants, dental assistants, dental technicians, and dental students. Demographic data and immunisation status, either by vaccination or by immunity after disease, were collected. Additionally, employers and employees were asked about their current workplace vaccination policy, including questions about information provided on the risk of hepatitis B (HBV) infection, whether HBV vaccination was compulsory and who paid for compulsory vaccinations.RESULTS: The overall response rate was 55.7%. Approximately half of the participants were dentists; only 17 technicians completed the questionnaire. The most common immunisation was for HBV (94.7% of participants). Only 19.2% of participants reported immunisation against human papillomavirus. Uncertainty over immunisation status was highest for Haemophilus influenzae type B (46.7%). Only a minority of participants (17.4%) received a yearly vaccination against seasonal influenza, whereas two-thirds never get vaccinated. The participants’ level of awareness related to the seven general vaccinations (HBV, influenza, measles, mumps, rubella, varicella, and tetanus) was medium to high, whereas their level of awareness related to vaccinations against HBV and influenza was medium. Half of the employees stated that they were informed about the risk of HBV at their current workplace and over three-quarters of employers indicated that they provided such information to their employees. Compulsory HBV vaccination was implemented at approximately half of the dental practices.CONCLUSION: The Swiss dental healthcare workers participating in this study had a medium level of awareness towards vaccinations. Almost all participants were vaccinated against HBV, but they were particularly hesitant about the seasonal influenza vaccination. As a considerable number of participants was unaware of their immunisation status, more comprehensive information on infectious diseases, vaccination and prevention is essential.